Risk factors for symptomatic venous thromboembolism following surgery for closed ankle fractures: A case-control study. Issue 6 (August 2020) - Stavem, Knut; Skjaker, Stein Arve; Hoel, Henrik; Naumann, Markus Georg; Sigurdsen, Ulf; Ghanima, Waleed; Utvåg, Stein Erik
Highlights: There is limited information on risk factors for VTE after surgery for ankle fractures. Increasing age was associated with VTE within 6 months of ORIF. Obesity was associated with VTE within 6 months of ORIF. The odds of VTE were lower with increasing comorbidity. The findings were based om multivariable analysis. Abstract: Background: We analyzed risk factors for venous thromboembolism (VTE) within 6 months after surgery for closed ankle fractures. Methods: This was a case-control study based on data from chart review in a cohort of patients having open reduction and internal fixation (ORIF) for closed ankle fractures in two large general hospitals 2009–2011. Cases with symptomatic VTE (pulmonary embolism or deep venous thrombosis) were identified in the cohort, and additional cases of VTE were identified by computerized search of discharge diagnoses in the same hospitals in 2004–2008 and 2012–2016. In total, we identified 60 cases with VTE and compared with 240 randomly selected controls among 998 patients without VTE in the cohort. Risk factors were assessed using logistic regression analysis. Results: Among cases, 27 (45%) had pulmonary embolism, 33 (55%) deep venous thrombosis. Those with VTE were older, had higher BMI, had more often a family history of VTE, and more often had antibiotic prophylaxis during surgery than controls. In multivariable logistic regression analysis age/10 (OR 25.75, 95%CI 3.52–188.44, p = 0.001), (age/10) 2 (OR 0.77, 95%CI 0.65–0.93, p = 0.005), BMI (1.15 per kg/m 2, 95%CI 1.07–1.24, p < 0.001) and Charlson comorbidity index ≥2 vs.0 (OR 0.27, 95%CI 0.08–0.92, p = 0.036) and 1 vs. 0 (OR 0.27, 95%CI 0.09–0.86, p = 0.026) were associated with VTE within 6 months of surgery. Conclusions: The odds of symptomatic VTE within 6 months of ORIF increased with increasing age and BMI, but were lower with increasing comorbidity.